A concise route towards isoflavans. (15th October 2020) - Basuli, Suchand; Chinnabattigalla, Sreenivasulu; Gupta, Kshitija; Gedu, Satyanarayana
Abstract: Isoflavans have gained considerable interest owing to their potential health benefits. Herein, we have presented a straightforward strategy for isoflavans synthesis. The strategy features an intermolecular [Cu]‐catalyzed arylation of malonates and an intramolecular [Pd]‐catalyzed Buchwald coupling of hydroxy tethered bromoarenes as the key transformations. This protocol enabled the synthesis of a variety of isoflavan analogs. Abstract :